Foreignness and Otherness in Selected Press Discourses about the Issues of Refugees - Księżyk, Felicja (Papers in Linguistics, 2019)
This article presents the results of the analysis of selected press discourses concerning current issues of refugees. The purpose of this article is to find answers to the following questions: 1) How is the refugee problem expressed linguistically in the selected collection of texts? 2) What characteristics do newspapers give to refugees and how are they judged? 3) What differences and similarities can be observed in the description of the issues concerning refugees based on the selected collections of texts?